2013
DOI: 10.1152/ajpgi.00402.2012
|View full text |Cite
|
Sign up to set email alerts
|

Role of the vagus in the reduced pancreatic exocrine function in copper-deficient rats

Abstract: Copper plays an essential role in the function and development of the central nervous system and exocrine pancreas. Dietary copper limitation is known to result in noninflammatory atrophy of pancreatic acinar tissue. Our recent studies have suggested that vagal motoneurons regulate pancreatic exocrine secretion (PES) by activating selective subpopulations of neurons within vagovagal reflexive neurocircuits. We used a combination of in vivo, in vitro, and immunohistochemistry techniques in a rat model of copper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
17
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(19 citation statements)
references
References 58 publications
2
17
0
Order By: Relevance
“…Finally, recent studies have also demonstrated in rats that copper deficiency, which causes a selective non inflammatory loss of pancreatic acinar tissue but leaves the islet of Langherans unaffected, diminishes the sensitivity of DMV neurons to CCK and PP, further supporting the notion that neurons responsive to these peptides specifically regulate PES [11]. These findings provide further evidence that pancreas-projecting DMV neurons comprise at least two subpopulations which modulate selectively exocrine or endocrine pancreatic functions.…”
Section: Neural Regulation Of Pancreatic Functionssupporting
confidence: 54%
See 2 more Smart Citations
“…Finally, recent studies have also demonstrated in rats that copper deficiency, which causes a selective non inflammatory loss of pancreatic acinar tissue but leaves the islet of Langherans unaffected, diminishes the sensitivity of DMV neurons to CCK and PP, further supporting the notion that neurons responsive to these peptides specifically regulate PES [11]. These findings provide further evidence that pancreas-projecting DMV neurons comprise at least two subpopulations which modulate selectively exocrine or endocrine pancreatic functions.…”
Section: Neural Regulation Of Pancreatic Functionssupporting
confidence: 54%
“…Recent data from our laboratory have provided further evidence that separate vagal pathways regulate PES and insulin release and that DMV neurons regulating these two functions can be distinguished based on their neurochemical and pharmacological properties [1,9,11]. We have demonstrated that CCK, PP and GLP-1 have both presynaptic and postsynaptic effects on pancreas-projecting DMV neurons [912].…”
Section: Neural Regulation Of Pancreatic Functionsmentioning
confidence: 93%
See 1 more Smart Citation
“…Previous studies on the anatomy and physiology of pancreatic innervation under physiological conditions (Figure 1), during enteropancreatic reflex, exocrine section, digestive hormone effects, or during acute pancreatitis and pancreatic nociception in mice, have laid the foundations for our current understanding of neuroplasticity in all pancreatic disorders. [1][2][3][4][5][6][7][8] In ceruletide-induced acute pancreatitis in mice, sensory dorsal root ganglia (DRG) neurons upregulate pain-associated and inflammation-associated ion channels such as transient receptor potential cation channel subfamily V member 1 (TRPV1; also known as transient receptor potential vanilloid 1) or TRP cation channel subfamily A member 1 (TRPA1) within the first 24 h. 9 The activation of these ion channels is known to induce the release of substance P from the projections of these neurons in the spinal cord, and antegrade or antidromic release of substance P into the pancreas. Substance P was shown to be the major mediator of 'neurogenic' inflammation in the pancreas via recruitment of inflammatory cells to the tissue and enhancing fluid extravasation.…”
Section: Introductionmentioning
confidence: 99%
“…, b ; Babic et al . ) and microinjections of these agents into the dorsal vagal complex (DVC) elicit changes in PES and insulin release (Jung et al . ; Viard et al .…”
Section: Introductionmentioning
confidence: 99%